Arduino-based design and implementation of experimental rooms with a trombe wall for solar cells applications - Raid W. Daoud; Obed Majeed Ali; Omer Khalil Ahmed; Ihab A. Satam (Bulletin of Electrical Engineering and Informatics, 2023)
The simplicity of design and construction following the researcher's or company's notion is the most typical description of solar panels. There will be a set of sensors in every design to derive information about the environment's shifting seasons and days. Two chambers of 1 m2 and 2 m in height were constructed for this study. A solar panel made from a unique exchangeable material has been installed instead of one of the walls, allowing a space between them for experimental reasons. Several temperature sensors were mounted inside and outside the chamber, as well as on the surface of the solar panel and within the air openings, in this work to record the temperature readings in various places. The used controller, an Arduino, is in charge of several operations, including controlling the solar panel's cooling device, reading and recording sensor data and storing it in RAM, controlling the orientation of the solar panel, controlling the vacuums, and regulating the on-off time of the motors. The findings show that by using sensor data, the system can keep the temperature constant when it is turned on. Additionally, the battery life will be preserved to the greatest extent feasible thanks to the well-balanced regulation of the loads.